Consortium urban operations, real estate capital interests, and urban master plans: Salvador, Bahia, Brazil, 2000-2016 - Cardoso Santos, André Luís; Rocha dos Santos, Ana (Geografares, 2025)
This article aims to analyze changes in the parameters guiding the application of Consortium Urban Operations (Operações Urbanas Consorciadas – OUCs) within the various Urban Development Master Plans (Planos Diretores de Desenvolvimento Urbano – PDDU) approved in Salvador, Bahia, from 2004 to 2016, emphasizing their relationship to private-sector interests. The analysis reveals a progressive alignment of this urban planning tool with real estate market demands, as explicitly articulated in the “Masterplan Salvador Capital Mundial”, a plan donated by the Baía Viva Foundation to the municipality and presented by the Salvador City Hall in 2010. The findings indicate that although OUCs have the potential to drive significant social transformations, in Salvador, this instrument has been consistently adapted to serve primarily the interests of real estate capital.